2013
DOI: 10.1073/pnas.1311133110
|View full text |Cite
|
Sign up to set email alerts
|

Entropic factors provide unusual reactivity and selectivity in epoxide-opening reactions promoted by water

Abstract: Despite the myriad of selective enzymatic reactions that occur in water, chemists have rarely capitalized on the unique properties of this medium to govern selectivity in reactions. Here we report detailed mechanistic investigations of a water-promoted reaction that displays high selectivity for what is generally a disfavored product. A combination of structural and kinetic data indicates not only that synergy between substrate and water suppresses undesired pathways but also that water promotes the desired pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…We hypothesize that this cation may coordinate to the substrate in different ways to cause conformational changes, which have previously been shown to affect the rate and selectivity of epoxy alcohol cyclizations. 34 Murai and co-workers have also shown that coordination of a Lewis acid to the substrate can influence the regioselectivity of epoxide-opening cascades. 5a In our case, coordination of the cation with the MOM ether and its neighboring epoxide may be responsible for the undesired exo cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that this cation may coordinate to the substrate in different ways to cause conformational changes, which have previously been shown to affect the rate and selectivity of epoxy alcohol cyclizations. 34 Murai and co-workers have also shown that coordination of a Lewis acid to the substrate can influence the regioselectivity of epoxide-opening cascades. 5a In our case, coordination of the cation with the MOM ether and its neighboring epoxide may be responsible for the undesired exo cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Jamison and coworkers have reported related catalytic functions of water in their epoxide-opening cascades to form ladder polyethers, with differential kinetic orders of hydrogen-bonding catalysis proposed to provide selectivity for competing endo and exo reaction manifolds. 27 Taken together, these studies reveal the dramatic and specific roles that simple solvents can play in hydrogen-bonding catalysis of epoxide-opening reactions and raise the possibility that specific solvent catalysis may play as yet unappreciated roles in other reactions as well.…”
Section: Mechanism Of Meoh-catalyzed Kinetic Spirocyclizationmentioning
confidence: 89%
“…Among our efforts is the development of directing-group free cascades that use THP or 1,3-dioxane templates. 11,12 The latter, in particular, can provide greatly-enhanced endo selectivity, with the 6-membered THP product favored under basic, acidic or neutral water conditions.…”
Section: Introductionmentioning
confidence: 99%